The Utilization of Cattle Manure Biogas as a Renewable Energy Solution and a Means to Improve Community Welfare in Kuripan Village, Karangawen District, Demak - Achmad Buchori; Dina Prasetyowati; Suwarno Widodo; Adhi Kusmantoro; Siti Maisyaroh Bakti Pertiwi (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2025)
Kuripan Village, located in Karangawen District, Demak, holds significant opportunities for renewable energy advancement through the optimal management of cattle waste. When left untreated, livestock waste can cause serious environmental pollution, while local households continue to depend largely on fossil-based energy sources for daily use. This community engagement project was designed to empower residents by converting cattle waste into biogas as a sustainable energy alternative. The initiative involved awareness campaigns, hands-on workshops for building biogas installations, and ongoing technical guidance in their operation and upkeep. Beyond energy generation, the project also emphasized the transformation of waste by-products into organic fertilizer and complementary livestock feed. This practice not only reduces feed costs but also improves animal nutrition, establishing a circular livestock system that supports eco-friendly farming. The outcomes revealed that villagers successfully constructed and operated biogas facilities independently. The generated biogas is used for cooking activities, while the remaining slurry and solids are applied as fertilizer and feed material. Overall, the program has reduced environmental waste and greenhouse gas emissions, decreased monthly household energy spending by IDR 60,000–90,000, and enhanced farmers’ quality of life. These results affirm that combining appropriate technology with active community involvement fosters sustainable and energy-resilient rural development.